Holographic effect through full parallax multi-viewpoint augmented reality with extended depth of field - Yoon, Jinho; Yoon, Ki-hyuk; Choi, Wonshik; Kim, Sung Kyu (Nature Publishing Group, 2026)
Augmented reality near eye display (AR NED) is highly promising for applications that integrate real-world environments with virtual imagery. However, their commercialization is currently limited by the vergence and accommodation conflict (VAC), which arises from the mismatch between binocular vergence depth and monocular focal depth. In this study, we show a holographic-like AR optical system that generates full parallax multi-viewpoint (FPMVP) with an extended depth of field, achieving sharp virtual images at the observer’s gaze depth and optical blur at other depths, without mechanical actuation or modification of optical components. This holographic-like visual effect effectively reduces VAC by providing monocular depth cues. Simultaneously, the extended depth of field of the FPMVP optical system enables resolution that satisfies the Rayleigh criterion over a broad range. The simple optical structure and excellent scalability of this technology demonstrate significant potential for future commercialization in the AR NED market.